Dilemma in management of spontaneous neck hematoma - Agarwal, Vaishali; Singh, Huidrom A.; Patil, Amol A.; Patil, Sushant; Shirodkar, Salil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Spontaneous neck hematoma is a rare but potentially life-threatening condition due to its risk of rapid airway compromise. It is most commonly associated with aneurysm, infection, thyroid or parathyroid tumors, or underlying coagulopathy, and may also occur in patients receiving anticoagulation or thrombolytic therapy. We report the case of an 87-year-old male with massive pulmonary embolism and deep vein thrombosis who developed a spontaneous cervical hematoma following catheter-directed thrombolysis with alteplase and systemic heparin. The patient presented with progressive neck swelling, ecchymosis, and airway deviation confirmed by contrast-enhanced computed tomography (CT) and flexible fiberoptic laryngoscopy. Airway protection was achieved with endotracheal intubation, and anticoagulation was withheld. He was managed conservatively with intravenous steroids and antibiotics. Extubation was carefully planned using cuff-leak testing, which was successful without the need for surgical intervention. The hematoma resolved gradually, and the patient recovered fully. This case underscores the importance of early recognition, multidisciplinary decision-making, and individualized airway management strategies in optimizing outcomes for spontaneous neck hematoma, especially in anticoagulated patients.